Conservative endometrioma surgery: The combined technique versus CO2-laser vaporization only (BLAST: Belgium LAser STudy): Clinical protocol for a multicenter randomized controlled trial - Celine Bafort; Sharon Lie Fong; Steffen Fieuws; Brecht Geysenbergh; Michelle Nisolle; Jean-Luc Squifflet; Linda Tebache; Christine Wyns; Christel Meuleman; Carla Tomassetti (PLoS ONE, 2025)
Background The surgical management of endometrioma(s) remains challenging. Although laparoscopic surgery is a well-established treatment of endometrioma(s), caution is required to minimize ovarian damage. Several surgical techniques have been described to treat endometrioma(s): classical cystectomy, ablative techniques, or a combination of both. As cystectomy is strongly associated with a reduction in ovarian reserve, this randomized controlled trial (RCT) aims to determine to what extent the two other surgical procedures may affect ovarian reserve by comparing changes in serum anti-Müllerian hormone (AMH) levels concentrations after each type of surgery. Methods This is a multicenter, non-blinded, RCT with parallel groups (group 1 (combined technique) versus group 2 (CO2 laser vaporization only)) and allocation 1:1. Four Belgian centers will be involved. Main inclusion criteria are symptomatic patients (pain and/or infertility), 18–40 years (both inclusive) with an endometriotic cyst (mean diameter of ≥ 2.5 cm and ≤ 8 cm) and AMH level ≥ 0.7 ng/mL. Suspicion of malignancy, a contralateral endometrioma of > 2 cm, use of gonadotrophin-releasing hormone (GnRH) analogues around timing of surgery or previous oophorectomy are exclusion criteria. The primary aim is the evaluation of the difference in serum AMH levels between baseline and 3 months postoperatively (or delta AMH). The secondary outcomes include differences in AMH levels at 6 and 12 months postoperatively, cyst recurrence rate, evolution of pain pattern and fertility outcomes. Discussion The present study will help us to answer the question on which surgical technique for endometrioma(s) has the most favorable outcome in patients wishing to preserve their reproductive potential. Trial registration ClinicalTrials.gov: NCT04151433. Registered on November 5th, 2019.